THYMUS PEPTIDES (THYMULIN, THYMOSIN ALPHA 1 AND THYMOSIN BETA 4) INHIBITING EFFECTS ON THE INTRINSIC BLOOD COAGULATION PATHWAY IN RATS - Negrin Negrev; Kiril Hristosov; Antoniya Hachmeryan; Yuri Nyagolov (Peytchinski Publishing, 2017)
Thymus peptides (thymulin, thymosin alpha 1 and thymosin beta 4) inhibiting effects on the intrinsic blood coagulation pathway in rats Background and purpose: Hemostasis is a basic homeostatic mechanism protecting the body from thrombosis or haemorrhage. A number of pathological conditions, including multiple endocrine disorders modulate the balance between pro- and anticoagulation factors and establish conditions of hyper- or hypocoagulability. Endocrine effects of thymus gland on blood coagulation are not completely elucidated, and data existing on the theme are relatively scarce and partially controversial. The present study was designed to investigate thymus peptides (thymulin, thymosin alpha 1 and thymosin beta 4) effects on key intrinsic pathway plasma clotting factors XII, XI, IX, X and activated partial thromboplastin time (aPTT) - a principal marker of blood coagulation via intrinsic pathway of hemocoagulation, in rats. Materials and methods: Plasma clotting factor activities and aPTT were studied on 52 male Wistar intact rats after 3 day s.c. application of the thymic peptides envisaged using routine kinetic coagulometry. Results of the study indicate a significant reduction of FXII activity by thymulin and thymosin alpha 1, and FXI and FIX activity by thymulin and thymosin beta 4. Conclusion: Upper results support the conclusion that thymus peptides thymulin, thymosin alpha 1 and thymosin beta 4 application in rats imposes a distinct tendency of hypocoagulability.